Improving the Forecasting of Financial Resources of Commercial Banks - Ortiqov Uygun Davlatovich (International Journal on Integrated Education, 2023)
This article examines the role of investment portfolio management in the effective management of bank financial resources, the state of investment portfolios of commercial banks and their impact on asset liquidity. According to the research materials and methods, the definitions and opinions given by a number of foreign and domestic economists-scientists on the topic were studied, and the author explained their meaning. In addition, the article provides proposals and practical recommendations for the development of a draft regulatory legal document on the management of financial resources of commercial banks of the Republic of Uzbekistan, and the development of a program of measures aimed at managing assets in commercial banks. As a result of the research, ways of expanding theoretical and practical knowledge of managing financial resources in commercial banks of our country, using convenient methods of their management, and studying subjects related to banking activities in higher educational institutions in the field of economics were studied. Suggestions are made for the preparation of teaching, curriculum, textbooks and study guides, as well as for their wide use as a resource for researchers conducting scientific research on the research topic. In particular, in the formation of digital assets in commercial banks, it is proposed to allow banks to participate in crypto-assets (tokens) in crypto-exchanges and to establish a crypto-depository in the structural structure of commercial banks.